Avaliação da estabilidade do canal fluvial em trechos adjacentes a pontes, pontilhões e bueiros na bacia hidrográfica do Paraná III - Oeste do Paraná - Bortoluzzi, Leandro Neri (2012)
The bridges and culverts alter the natural conditions of rivers, causing changes in fluvial processes. The level of stability of river banks and beds around crossing structures was evaluated in the Paraná III watershed, Western region of Paraná State (Brazil), adopting the methodology of Johnson (2006). The study area is characterized by outcrops of basaltic rocks of Cretaceous age. The degree of channel stability was analyzed at 46 structures (18 bridges, 15 culverts box, 7 culverts pipe and 6 small bridges). We selected all crossings structures located in the Paraná Basin III along paved roads, positioned outside the urban area. Among the crossings structure, 14 were classified as excellent level of stability and level 32 as good. There was no point with fair or poor stability. The predominance of soils with low erodibility (Oxisols and Ultisols) derived from basaltic rocks provide greater stability to streams banks which mostly show vertical phases. It was noted that in culverts (box and pipe), the stability of channels tends to lower than the bridges.